The Improvement of Lipid Profiles and Glucose Resistance of Hypercholesterolemic Rats using Tempeh Flour Based-Yoghurt Complemented with Red Pitaya Peel Extract - Nugraheni, Kartika; Putriningtyas, Natalia Desy; Fernando, G. S.N.; Bintari, Siti Harnina (Biosaintifika: Journal of Biology & Biology Education, 2023)
Tempeh flour is potentially a substitute material in making yoghurt that provides bioactive for improving cardiovascular health. It is also suitably combined with antioxidant sources, such as red pitaya peel extract, which is well known for inhibiting metabolic inflammation. This study aims to analyze the effectiveness of tempeh flour-based yoghurt complemented with red pitaya peel extract in improving lipid profiles and glucose tolerance in hypercholesterolemic rats. A total of 36 male Wistar rats were used and divided into six different groups: regular diet (ND) and five high-fat-diet rat groups treated with no supplementation (HFD); diary-based yoghurt with lactic acid bacteria (YBAL); commercial yoghurt (YB); tempeh flour based-yoghurt with lactic acid bacteria (SY); and tempeh flour based yoghurt complemented with red pitaya peel extract (SDS). The supplementation of each treatment group was given a dose of 3.6 ml/ KgBW/ day as a single dose for 28 days. The blood sample was collected from sinus orbitalis and then used for lipid profile, glucose, liver enzyme analysis, and statistical analysis using ANOVA. The result shows that glucose levels increased significantly in all groups, except HFD groups, and there is no significant difference between normal and yoghurt treatment groups. However, yoghurt and red pitaya peel extract supplementation significantly decrease LDL-C and increase HDL-C levels while improving liver condition during hypercholesterolemia. In conclusion, tempeh flour-based yoghurt complemented with red pitaya peel extract can improve lipid profile and liver health in hypercholesterolemia rats. Therefore, further research on metabolism pathways is needed to develop potential nutraceutical products for people with hypercholesterolemia.